Studi Penentuan Desa Pusat Pertumbuhan Dalam Pengembangan Wilayah di Kecamatan Salomekko Kabupaten Bone - St Haerunnisa Nas; Murshal Manaf; Rusneni Ruslan (Fakultas Teknik Universitas Bosowa, 2023)
The purpose of this study was to examine villages that have the potential to become growth center villages in Salomekko District and to identify development strategies for growth center villages in regional development in Salomekko District. The variables used in the study consisted of 6 (eight), namely : (1) Village Potential , (2) Supporting facilities for the development of production and services, (3) Community Institutions, (4) Supporting facilities for services, (5) Population Density, (6) Accessibility,. The analytical method used is the Quantitative Descriptive Analysis Method (Scoring) and SWOT analysis. Based on the results of the analysis of the results obtained from the 6 (six) aspects of determining the DPP, Pancaitana Village received the highest final total score of 11.33. The strategy used in the development of the selected DPP areas is assistance from the local government to accelerate regional development, the availability of complete infrastructure facilities to make it easier for the community to develop tourism potential, improve the quality of human resources, and accelerate port construction to improve the community's economy